The diffusion of cholera in Egypt, 1947: a time-space analysis of one of the largest single outbreaks in the twentieth century. (October 2016) - Smallman-Raynor, Matthew; Cliff, Andrew D.
Abstract: The epidemic of cholera that spread through Egypt in the latter months of 1947 was one of the largest single outbreaks of the disease in the twentieth century. Using a swash–backwash model, this paper examines the geographical wave-like spread and subsequent retreat of the epidemic from an apparent origin in the settlements and prisoner-of-war camps of the Nile Delta area to reach its maximum geographical extent some six weeks later at Aswan (850 km away). Our results demonstrate the very rapid spatial advance of the epidemic wave through the provinces and governorates of Egypt, with an approximately linear sequence of progression up the Nile. Superimposed on this national pattern are pronounced differences in the rate of epidemic advance in the traditional geographical divisions of Lower and Upper Egypt. Alternative visualisations of the cholera spaces of Egypt, using techniques of multidimensional scaling (MDS) and cluster analysis, underscore the differential patterns of cholera transmission in these areas of the country. The patterns are interpreted in relation to a vigorous control effort that included restrictions on public transport, patient isolation, contact tracing and mass vaccination of the entire population exposed to risk of infection. Highlights: Geographical transmission of the epidemic is modelled using robust spatial methods. The epidemic spread wave-like up the Nile from the Nile Delta area. The rate of epidemic propagation differed in the divisions of Lower and Upper Egypt. Country-wide spread had been achieved before vaccines became available in quantity.